2020
DOI: 10.1177/0883073820930487
|View full text |Cite
|
Sign up to set email alerts
|

Disability Prediction by Early Hammersmith Neonatal Neurological Examination: A Diagnostic Study

Abstract: Background and Objectives: Hammersmith Neonatal Neurologic Examination (HNNE) is used to identify term and preterm infants at risk of neurodevelopmental disability. The test is recommended at corrected term age in preterm; and around 2 weeks postnatal age in term neonates. As the current trend is to discharge based on physiological stability, it may not be feasible to perform HNNE at recommended age. The authors investigated whether predictive ability of the test for neurodevelopmental disability remained unch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 14 publications
4
28
0
Order By: Relevance
“…This is consistent with current evidence, which suggests that the HNNE performed at two weeks post-term in term infants, or at termcorrected age in preterm infants, is highly predictive of a neurodevelopmental deficit [28]. A recent study by Venkata et al found that the HNNE had an equivalent predictive value for predicting CP at 1 year when performed early (i.e., before discharge in preterm infants) and when performed at the recommended age as outlined above [28]. The HNNE had a sensitivity of 50-64% and specificity of 73-77% with a global optimality score cut-off of 32.5, as per Dubowitz [19,28].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with current evidence, which suggests that the HNNE performed at two weeks post-term in term infants, or at termcorrected age in preterm infants, is highly predictive of a neurodevelopmental deficit [28]. A recent study by Venkata et al found that the HNNE had an equivalent predictive value for predicting CP at 1 year when performed early (i.e., before discharge in preterm infants) and when performed at the recommended age as outlined above [28]. The HNNE had a sensitivity of 50-64% and specificity of 73-77% with a global optimality score cut-off of 32.5, as per Dubowitz [19,28].…”
Section: Discussionsupporting
confidence: 92%
“…However, this association was not statistically significant ( p = 0.05, 95% CI [0.78, 1.00]). This is consistent with current evidence, which suggests that the HNNE performed at two weeks post-term in term infants, or at term-corrected age in preterm infants, is highly predictive of a neurodevelopmental deficit [ 28 ]. A recent study by Venkata et al found that the HNNE had an equivalent predictive value for predicting CP at 1 year when performed early (i.e., before discharge in preterm infants) and when performed at the recommended age as outlined above [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…The HNNE was selected due to its wide use in assessment of neurological behavior in multiple populations ( Romeo et al. 2011 ; Venkata et al. 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In moderate-to-late preterm infants HNNE scores were associated with an increased risk of cognitive delay at 2 years, but not with motor and language outcome [77]. In a mixed group of infants mostly comprising preterm infants, HNNE predicted adverse neurodevelopmental outcome at 1 year with sensitivities of 50%-64% and specificities of 73%-77% [79]. A study performed in the prehypothermia era in infants with HIE indicated that HNNE has good predictive properties [81].…”
Section: Neurological Assessmentsmentioning
confidence: 97%
“…It is also advised to perform HNNE in preterm infants at TEA. Yet, the study of Venkata et al [79] suggests that the predictive properties of HNNE performed around 36 weeks, that is, at an age that most preterm infants are still in the hospital, is similar to that of HNNE at TEA. The predictive values of HNNE in preterm infants vary.…”
Section: Neurological Assessmentsmentioning
confidence: 99%